Senior Students' Perceptions of Entering a Research Community. (July 2017) - Brent, Doug
Most of the literature on the assignment traditionally called the research paper focusses on first-year students, and often centers on what they don't know or can't do. This article seeks to expand the conversation to one about the skills and knowledge displayed by senior students, and about their perceptions of the universe of academic research and their place in it. It does so by means of a qualitative study of 13 senior students at the University of Calgary. Through interviews, I probe their understanding of their own research processes, how they think they learned to do what they do, and, most important, their understanding of what it means to conduct academic research.